2020
DOI: 10.1177/0267659120901413
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic effects on gas exchange performance of membrane oxygenator and blood coagulation during cardiopulmonary bypass in pigs

Abstract: Introduction: Whether hypothermic cardiopulmonary bypass could attenuate both blood coagulation and platelet activation compared to normothermic cardiopulmonary bypass remains elusive. Methods: Biocompatibility of a polymer-coated cardiopulmonary bypass circuit was comparatively assessed by plasma proteomics between juvenile pigs undergoing hypothermic (23°C) cardiopulmonary bypass and those undergoing normothermic (37°C) cardiopulmonary bypass (n = 6, respectively). Plasma samples were taken three times: 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is noteworthy that baseline levels of β-TG and sP-selectin in porcine plasma were much lower than those described for humans 28 , 29 while correlating with recently reported porcine ones. 30 We also showed that surface expression of P-selectin (CD62P) on platelets, as monitored by flow cytometry, was not elevated after blood recirculation within the device-propelled loops. Conversely, a mild downregulation of P-selectin surface expression occurred during long-term shear exposure ( Figure 3 B ).…”
Section: Discussionmentioning
confidence: 76%
“…It is noteworthy that baseline levels of β-TG and sP-selectin in porcine plasma were much lower than those described for humans 28 , 29 while correlating with recently reported porcine ones. 30 We also showed that surface expression of P-selectin (CD62P) on platelets, as monitored by flow cytometry, was not elevated after blood recirculation within the device-propelled loops. Conversely, a mild downregulation of P-selectin surface expression occurred during long-term shear exposure ( Figure 3 B ).…”
Section: Discussionmentioning
confidence: 76%
“…Normothermia had no effect on development of postoperative stroke, atrial fibrillation, renal failure, or mortality ( 248 ). A large-animal study recently showed hypothermic CPB attenuated platelet degranulation and coagulopathy and better maintained oxygenator performance in swine ( 249 ). Several RCTs studying pediatric populations showed normothermic CPB as noninferior to hypothermic CPB with endpoints including inotrope duration, intubation time, hospital stay, and early neurodevelopmental outcomes in low-risk populations ( 250 , 251 ).…”
Section: Strategies To Modulate Cpb-associated Inflammatory Responsementioning
confidence: 99%